Tuesday

March 3, 2015

March 3, 2015

Posted by **Susie** on Friday, May 30, 2008 at 2:09pm.

x + 6y = -4 3x - 4y = 10

- Math -
**Damon**, Friday, May 30, 2008 at 2:48pmfrom the first equation:

x = -(6y+4)

substitute that for x in the second equation

-3(6y+4) -4y = 10

-18y -12 -4y = 10

-22 y = 22

y = -1

now go back and get x

x = -(6*-1 + 4)

x = - (-2)

x = 2

check

2 + 6*-1 = -4 sure enough

3*2 -4*-1 = 10 yes

**Answer this Question**

**Related Questions**

Math - 1) Find the solution to the following system of two linear equations, if ...

Math - Determine if f could be a linear function x 0 1 2 3 4 f(x) 3 5 7 11 15 is...

Algebra - Suppose a linear system of equations has 2012 equations and 2013 ...

Algebra 1 - 1. What is the domain of the function {(18,34),(22,64),(94,36),(11,...

Grade 10 Math - Write an equation that forms a system of equations with x + y = ...

Math - 1.) Can a system of linear equations have exactly two solutions? A. True ...

Math - Use the substitution method to solve the following system of linear ...

Math - Consider the following 2x2 system of linear equations, x + y = 3 x + (a^2...

Math - True or false, A solution of a system of linear equations is an ordered ...

Linear algebra - Consider for every real number a the linear system of equations...